2002
DOI: 10.1016/s0886-3350(02)01507-9
|View full text |Cite
|
Sign up to set email alerts
|

Induced optical aberrations following formation of a laser in situ keratomileusis flap

Abstract: Flap formation during LASIK can modify the eye's existing natural higher-order aberrations (especially spherical and coma-like aberrations along the axis of the flap's hinge), while visual acuity and refractive error remain unaffected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
97
1
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(107 citation statements)
references
References 13 publications
6
97
1
3
Order By: Relevance
“…For 5.0 mm pupils, PRK induces more coma and third-order aberrations, although the low pr 2 (less than 0.01) indicates that the percentage of unexplained variance that can be attributed to surgical method (PRK versus LASIK) was very low. Flap production in LASIK induces higher-order aberrations, including coma and spherical aberrations, 7,8,27,28 which were consistent in part with our findings. Also, most of the patients in the present study were highly myopic with mean spherical equivalent of -7.32 D. Even so, post-operative higherorder aberrations in patients receiving PRK or LASIK differed little.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For 5.0 mm pupils, PRK induces more coma and third-order aberrations, although the low pr 2 (less than 0.01) indicates that the percentage of unexplained variance that can be attributed to surgical method (PRK versus LASIK) was very low. Flap production in LASIK induces higher-order aberrations, including coma and spherical aberrations, 7,8,27,28 which were consistent in part with our findings. Also, most of the patients in the present study were highly myopic with mean spherical equivalent of -7.32 D. Even so, post-operative higherorder aberrations in patients receiving PRK or LASIK differed little.…”
Section: Discussionsupporting
confidence: 91%
“…For example, some studies showed that all laser refractive surgery, including PRK and LASIK, will increase both higher-order aberrations of the corneal surface and the total wavefront aberrations even with a flying-spot excimer laser. [2][3][4][5][6] Furthermore, flap creation during LASIK can induce aberrations 7,8 and some other studies have shown that LASIK induces more aberrations than PRK and laser epithelial keratomileusis (LASEK). 3,9,10 These studies focused on the cornea because it is the target for laser ablation and accounts for most induced higher-order aberrations.…”
mentioning
confidence: 99%
“…2,3 Laser ablation methods also find widespread use in the micro-structuring and patterning of polymers and wide band gap materials like silicon and fused silica, in removal of biological (e.g. corneal) tissue, 4 and are now even being applied to surface cleaning of delicate artwork. 5 The realisation that laser ablation methods could provide a means of ejecting intact molecules -even large biomolecules -into the gas phase helped spawn novel analytical techniques like matrix assisted laser desorption/ionisation (MALDI) which has now come to be seen as essential in broad areas of the life sciences.…”
Section: Simon Henley Completed His Phd In the Physics Department Of mentioning
confidence: 99%
“…Vertical coma decreased in the study group and was not significant when compared with the control group at 2 months after the flap cut and 3 months postablation. Pallikaris and coworkers 21 noted an increase in horizontal coma after using a microkeratome that created a nasal hinge, suggesting the position of the flap hinge may influence the type(s) of aberrations induced after the incision. An analogous finding of induced vertical coma was not found for our cohort of patients after creating a flap with a superiorly located hinge.…”
mentioning
confidence: 99%